2014
DOI: 10.1016/j.mjafi.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of central venous catheter-related bloodstream infection without catheter removal: A prospective observational study

Abstract: We recommend combining semiquantitative cultures and peripheral blood cultures to screen for CR-BSI, leaving differential quantitative blood cultures as a confirmatory and more specific technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…There are therefore implications for nursing care, in relation to prevention of MDR‐GNB in patients with in‐dwelling central venous catheters. Central venous catheter‐related infections enter the body through intra luminal, extra luminal, and haematogenous routes (Kumar, Sharma, Jaideep, & Hazra, ), making it essential to ensure strict adherence to aseptic technique, and use of appropriate cleansing (such as iodine or alcohol disinfection) prior and in relation to skin puncture to prevent iatrogenic infection. In mechanically ventilated patients, incidence rates of ventilator‐associated pneumonia of between 9% and 27%, and mortality rates between 25% and 50%, have been reported (Tseng et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are therefore implications for nursing care, in relation to prevention of MDR‐GNB in patients with in‐dwelling central venous catheters. Central venous catheter‐related infections enter the body through intra luminal, extra luminal, and haematogenous routes (Kumar, Sharma, Jaideep, & Hazra, ), making it essential to ensure strict adherence to aseptic technique, and use of appropriate cleansing (such as iodine or alcohol disinfection) prior and in relation to skin puncture to prevent iatrogenic infection. In mechanically ventilated patients, incidence rates of ventilator‐associated pneumonia of between 9% and 27%, and mortality rates between 25% and 50%, have been reported (Tseng et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…With P > 0.05 and 95% CI containing 0 and 1, the results of these meta-analyses were shown to be relatively stable and that publication bias was unlikely to have affected the results. routes (Kumar, Sharma, Jaideep, & Hazra, 2014), making it essential to ensure strict adherence to aseptic technique, and use of appropriate cleansing (such as iodine or alcohol disinfection) prior and in relation to skin puncture to prevent iatrogenic infection. In mechanically ventilated patients, incidence rates of ventilator-associated pneumonia of between 9% and 27%, and mortality rates between 25% and 50%, have been reported (Tseng et al, 2012).…”
Section: Publication Biasmentioning
confidence: 99%
“…These techniques, particularly differential time to positivity (DTP), have shown good sensitivity and specificity 26,35 in both longand short-term catheters 30,35 . Studies also demonstrate good clinical utility of concurrent DTP and semi-quantitative superficial cultures of insertion site skin and catheter hub for both VADassociated BSI and catheter tip colonisation in VADs of critically ill patients 27,36 . Furthermore, a retrospective study spanning 9 years demonstrated no difference in in-hospital mortality between conservative VAD-associated infection diagnostic methods and conventional methods involving removal of the VAD 28 .…”
Section: Diagnostic Techniquesmentioning
confidence: 79%
“…A study conducted by Kumar et al . [ 21 ] demonstrated that cultures of the blood from the CVC port and periphery had negative predictive values of 86.67% and 84.38%, respectively, for the catheter origin of BSI. The classic reference method to confirm CR-BSI consists of concomitant isolation of the same microorganism from blood samples and the catheter tip.…”
Section: Discussionmentioning
confidence: 99%